Electrophysiological and histomorphological changes of cochlea in miniature pigs after abrasion of round window niches. (1st June 2021) - Liu, Qian; Guo, Weiwei; Yang, Shiming; Ji, Xiaojun; Lin, Chang; Chen, Wei
Abstract: Background: In operations of cochlea implantation (CI), many surgeons choose to drill a window on the bone wall of cochlea basic rotation, when more and more patients receive CI with residual hearing, what damage this step would result in is unclear. Objective: To study the effect to inner ear hair cells which is caused by drilling during CI. Methods: 6 miniature pigs are equally divided into two groups, Round window niche of each pig in the experimental group was milled, while the pigs in control group wasn't. After implanting depth of 6.5, 11.5 and 20 mm, round window electrocochleography was recorded to analyze the change of cochlea microphonic (CM) potentials respectively, histomorphological changes was observed. Results: Thresholds of CM in experimental group were higher than that of control group at different depth, amplitudes were smaller. In further group, cilia of inner hair cells (IHC) at bottom rotation were significantly damaged. After operation, ABR hearing threshold of experimental group was higher, differences at low frequency region were more obvious. Conclusions: Damage caused by mulling round window niche may seriously affect the function of the hair cells. Damage of the IHC is greater than OHC. CI through round window may protect residual hearing.